2015
DOI: 10.1179/1743132815y.0000000055
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation of the glycyl-tRNA synthetase (GARS) gene associated with Charcot–Marie–Tooth type 2D in a Chinese family

Abstract: The c.999G>T mutation is a novel mutation of the GARS gene that has not been previously reported. The phenotype of this family is CMT2D, which is first reported in Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…HMN5A is phenotypically similar to axonal CMT, but without sensory involvement . A series of follow‐up studies reported additional mutations (A57V, D146N, D146Y, S211F, L218Q, M238R, P244L, E279D, I280F, H418R, D500N, G598A), adding up to 16 distinct mutations , distributed throughout the primary GlyRS sequence (Fig. B).…”
Section: Dominant Mutations In Trna Synthetase Genes Cause Charcot‐mamentioning
confidence: 93%
“…HMN5A is phenotypically similar to axonal CMT, but without sensory involvement . A series of follow‐up studies reported additional mutations (A57V, D146N, D146Y, S211F, L218Q, M238R, P244L, E279D, I280F, H418R, D500N, G598A), adding up to 16 distinct mutations , distributed throughout the primary GlyRS sequence (Fig. B).…”
Section: Dominant Mutations In Trna Synthetase Genes Cause Charcot‐mamentioning
confidence: 93%
“…The ability of patients with CMT2D to sense vibration is most impaired, followed by light touch, temperature, and pain (20). Furthermore, patients with CMT2D display deficits in deep tendon reflexes of the extremities (22,23), whereas reflexes of patients with dSMA-V remain relatively unperturbed (4,24), implicating defective relay arc afferents rather than efferents. CMT2D sensory defects are dependent on disease severity, but not duration, whereas patients with dSMA-V are refractory to sensory pathogenesis, suggesting that, similar to other neurological diseases (25), the two disorders lie along a spectrum and that diseasemodifying loci may dictate these differences (20).…”
Section: Significancementioning
confidence: 99%
“…A second major conundrum in GlyRS-associated neuropathy is why some patients with dominant GARS mutations and diagnosed with the allelic neuropathy distal spinal muscular atrophy type V (dSMA-V, OMIM 600794) (4), lack the distinguishing mild-tomoderate sensory involvement typical of CMT2D (20)(21)(22)(23). The ability of patients with CMT2D to sense vibration is most impaired, followed by light touch, temperature, and pain (20).…”
Section: Significancementioning
confidence: 99%
“…A second major conundrum in GlyRS-associated neuropathy is why some patients with dominant GARS mutations, diagnosed with the allelic neuropathy distal spinal muscular atrophy type V (dSMA-V, OMIM 600794) (4), lack the distinguishing mildto-moderate sensory involvement typical of CMT2D (19)(20)(21)(22). The ability of CMT2D patients to sense vibration is most impaired, followed by light touch, temperature, and pain (19).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of CMT2D patients to sense vibration is most impaired, followed by light touch, temperature, and pain (19). Furthermore, CMT2D patients display deficits in deep tendon reflexes of the extremities (21,22), while reflexes of dSMA-V patients remain relatively unperturbed (4,23), implicating defective relay arc afferents rather than efferents. CMT2D sensory defects are dependent on disease severity not duration, while dSMA-V patients are refractory to sensory pathogenesis, suggesting that the two disorders lie along a spectrum and that disease-modifying loci may dictate these differences (19).…”
Section: Introductionmentioning
confidence: 99%